Search for exclusive Higgs and Z boson decays to ϕγ and ργ with the ATLAS detector - Aaboud, Morad; Anders, Christoph; Andrei, George Victor; Antel, Claire; Bolz, Arthur; Brandt, Oleg; Djuvsland, Julia Isabell; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Geisler, Manuel Patrice; Jongmanns, Jan; et al. (Journal of high energy physics, 2018)
A search for the exclusive decays of the Higgs and Z bosons to a φ or ρ meson and a photon is performed with a pp collision data sample corresponding to an integrated luminosity of up to 35.6 fb−1 collected at √s = 13 TeV with the ATLAS detector at the CERN Large Hadron Collider. These decays have been suggested as a probe of the Higgs boson couplings to light quarks. No significant excess of events is observed above the background, as expected from the Standard Model. Upper limits at 95% confidence level were obtained on the branching fractions of the Higgs boson decays to φγ and ργ of 4.8 × 10−4 and 8.8 × 10−4, respectively. The corresponding 95% confidence level upper limits for the Z boson decays are 0.9 × 10−6 and 25 × 10−6 for φγ and ργ, respectively.
The ATLAS Collaboration: M. Aaboud, C.F. Anders, V. Andrei, C. Antel, A.E. Bolz, O. Brandt, J. Djuvsland, M. Dunford, D.E. Ferreira de Lima, S. Franchino, M.P. Geisler, J. Jongmanns, E.-E. Kluge, M. Kolb, M. Lisovyi, K. Meier, H. Meyer Zu Theenhausen, D.I. Narrias Villar, M. Sahinsoy, A. Schoening, H.-C. Schultz-Coulon, T.M. Spieker, R. Stamen, P. Starovoitov, S. Suchek, S.M. Weber, M. Wessels [und 2876 weitere]
Gesehen am 02.05.2025